Collection of the Lupinus genus in Morocco - Thami Alami I.; Al Faiz C.; Papineau J.; Huyghe C. (Réhabilitation des pâturages et des parcours en milieux méditerranéens, 2004)
Two collections of lupin species were obtained in Morocco in 1998 and 1990 as part of the effort to preserve genetic resources. Spontaneous and traditionally-grown populations of L. luteus, L. angustifolius and L. albus were examined. In 1998, twenty-six soil samples and 44 grain samples from the three species (L. cosentinii, L. luteus and L. albus) were collected. In 1999, the north of the country (Rif) as well as the area of the Middle and High Atlas were prospected. 49 samples of 5 species (L. cosentinii, L. atlanticus, L. luteus, L. angustifolius and L. albus) were collected. Accessions were studied in Morocco and France in order to describe their main traits.
11. Réunion du Sous-Réseau Ressources Fourragères Méditerranéennes du Réseau Coopératif Interrégional FAO-CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 2002/10/29-2002/11/01, Djerba (Tunisia)